The Effect Of Transformational Leadership On Employee Performance Intervened By Motivation And Work Discipline In The Regional Technical Implementation Unit Of Public Works And Spatial Planning Binjai Public Works And Spatial Planning Office Of North Suma - Swandi Pinem; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of transformational leadership on employee performance with work discipline and motivation as intervening variables in the Binjai Regional Technical Implementation Unit of the Public Works and Spatial Planning Office of North Sumatra Province. The research method used is quantitative with Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS). The research data shows that transformational leadership has a positive and significant influence on work discipline with an influence coefficient of 0.777, T-Statistic of 16.266 (> 1.96), and P-Value of 0.000 (< 0.05). In addition, transformational leadership also has a significant influence on motivation with an influence coefficient of 0.897, T-Statistic of 49.932 (> 1.96), and P-Value of 0.000 (< 0.05). Work discipline was proven to have a positive and significant influence on employee performance with an influence coefficient of 0.538, T-Statistic of 4.688 (> 1.96), and P-Value of 0.000 (< 0.05). Motivation also has a significant influence on employee performance with an influence coefficient of 0.329, T-Statistic of 2.078 (> 1.96), and P-Value of 0.040 (< 0.05). The indirect influence of transformational leadership on employee performance through work discipline is also significant, with an influence coefficient of 0.418, T-Statistic of 4.442 (> 1.96), and P-Value of 0.000 (< 0.05). Similarly, the indirect influence of transformational leadership on employee performance through motivation proved significant, with an influence coefficient of 0.295, T-Statistic of 2.058 (> 1.96), and P-Value of 0.042 (< 0.05). These results show that work discipline and motivation function as intervening variables that strengthen the relationship between transformational leadership and employee performance. This research provides important insights into how transformational leadership styles can influence key elements of human resources such as work discipline, motivation, and performance, and provides practical guidance for organizations to improve productivity.